2021
DOI: 10.1111/dmcn.14903
|View full text |Cite
|
Sign up to set email alerts
|

Childhood arterial ischemic stroke due to mineralizing angiopathy: an 18‐year single‐center experience

Abstract: Mineralizing angiopathy is a unique, age‐specific stroke syndrome characterized by basal ganglia infarction and lenticulostriate calcification after minor head injury in early childhood. There is limited understanding of the pathophysiology, course, and clinical outcome of this syndrome. We describe the clinical and radiographical phenotype of a single‐center, consecutively enrolled cohort of children with mineralizing angiopathy from January 2002 to January 2020 and provide a comparative analysis to previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A review of initial and follow-up imaging showed subtle hyperdensities in the bilateral basal ganglia, suggesting possible mineralizing angiopathy of the lenticulostriate arteries, which is associated with basal ganglia ischemic stroke and hemorrhage after minor trauma, typically in younger children. 50 reported in cardioembolic stroke in adults and in children. [18][19][20] The safe timing of starting or resuming anticoagulation is a frequent question in children after cardioembolic stroke, particularly those requiring procedures, based on the increased incidence of hemorrhagic transformation reported in adults on anticoagulation.…”
Section: What About the Next 24 Hours?mentioning
confidence: 99%
See 1 more Smart Citation
“…A review of initial and follow-up imaging showed subtle hyperdensities in the bilateral basal ganglia, suggesting possible mineralizing angiopathy of the lenticulostriate arteries, which is associated with basal ganglia ischemic stroke and hemorrhage after minor trauma, typically in younger children. 50 reported in cardioembolic stroke in adults and in children. [18][19][20] The safe timing of starting or resuming anticoagulation is a frequent question in children after cardioembolic stroke, particularly those requiring procedures, based on the increased incidence of hemorrhagic transformation reported in adults on anticoagulation.…”
Section: What About the Next 24 Hours?mentioning
confidence: 99%
“…A review of initial and follow-up imaging showed subtle hyperdensities in the bilateral basal ganglia, suggesting possible mineralizing angiopathy of the lenticulostriate arteries, which is associated with basal ganglia ischemic stroke and hemorrhage after minor trauma, typically in younger children. 50…”
Section: What Is the Role Of Thrombolysis In Childhood Stroke?mentioning
confidence: 99%